Employers' Associations and Industrial Relations : A Comparative Study - Thwaites, James (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Employers' Associations and Industrial Relations : A Comparative Study," by John P. Windmuller & Alan Gladstone.